Validation of the Japanese Version of the Multidimensional Measure of Family Supportive Supervisor Behaviors (FSSB-J) - Eguchi, Hisashi; Kachi, Yuko; Koga, Hayami K.; Sakka, Mariko; Tokita, Masahito; Shimazu, Akihito (Frontiers in Psychology, 2019)
Objective: The aim of the current study was to validate the Japanese version of the family supportive supervisor behaviors (FSSB-J) measure. FSSB is conceptualized as a multidimensional, superordinate construct constituted of four dimensions; emotional support, instrumental support, role modeling behaviors, and creative work-family management. Methods: The Japanese translated and back-translated FSSB-J questionnaire was administered to 1,670 men and women aged 20–59 who were registered with a Japanese online survey company in November 2017. The data were then divided into independent explorative and confirmative samples. Exploratory and confirmatory factor analyses were performed to evaluate the factorial validity of the FSSB-J. Construct validity was assessed with the potential consequences of FSSB (e.g., work-family spillover, work engagement, intention to leave, job satisfaction, and psychological distress) and convergent validity was assessed using similar concepts (e.g., organizational justice and social support). Internal consistency and test-retest reliability was examined to evaluate the reliability of the four dimensions of the FSSB. Results: An exploratory factor analysis extracted a two-factor solution. A series of confirmatory factor analyses revealed that the four-factor model fitted the data best. Construct and convergent validity were generally in line with our expectations. Cronbach’s α coefficient and test-retest reliability were sufficient for each of the four dimensions of the FSSB. Conclusions: This study suggests that FSSB-J is an adequate measure of FSSB in the Japanese context.